Reassessing the approach to informed consent: the case of unrelated hematopoietic stem cell transplantation in adult thalassemia patients. - Pisu, S; Caocci, G; d'Aloja, E; Efficace, F; Vacca, A; Piras, E; Orofino, MG; Addari, C; Pintor, M; Demontis, R; Demuru, F; Pittau, MR; et al. (BioMed Central, 2014)
INTRODUCTION: The informed consent process is the legal embodiment of the fundamental right of the individual to make decisions affecting his or her health., and the patient's permission is a crucial form of respect of freedom and dignity, it becomes extremely important to enhance the patient's understanding and recall of the information given by the physician. This statement acquires additional weight when the medical treatment proposed can potentially be detrimental or even fatal. This is the case of thalassemia patients pertaining to class 3 of the Pesaro classification where Allogenic hematopoietic stem cell transplantation (HSCT) remains the only potentially curative treatment. Unfortunately, this kind of intervention is burdened by an elevated transplantation-related mortality risk (TRM: all deaths considered related to transplantation), equal to 30% according to published reports. In thalassemia, the role of the patient in the informed consent process leading up to HSCT has not been fully investigated. This study investigated the hypothesis that information provided by physicians in the medical scenario of HSCT is not fully understood by patients and that misunderstanding and communication biases may affect the clinical decision-making process. METHODS: A questionnaire was either mailed or given personally to 25 patients. A second questionnaire was administered to the 12 physicians attending the patients enrolled in this study. Descriptive statistics were used to evaluate the communication factors. RESULTS: The results pointed out the difference between the risks communicated by physicians and the risks perceived by patients. Besides the study highlighted the mortality risk considered to be acceptable by patients and that considered to be acceptable by physicians. CONCLUSIONS: Several solutions have been suggested to reduce the gap between communicated and perceived data. A multi-disciplinary approach may possibly help to attenuate some aspects of communication bias. Several tools have also been proposed to fill or to attenuate the gap between communicated and perceived data. But the most important tool is the ability of the physician to comprehend the right place of conscious consent in the relationship with the patient.